CORRELATION ANALYSIS OF BEE VISITATION ON PLANTS IN KITADAN VALLEY TO DETERMINE KEYSTONE SPECIES USING FOREST GRAPH AND CENTRALITY MEASUREMENTS - Athayasari, Amanda
Keystone species is a species whose position in the ecosystem cannot be replaced by other species. The determination of keystone species can be done by looking at the relationship between species in a habitat. The data consisted of bee visitation to plants in the Kitadan Valley, Japan. Observations were carried out from April to November 2003-2006. The method used in determining keystone species by using forest graphs from all of the minimum spanning tree and centrality measurements. Forest graphs obtained from correlation matrix which transformed into adjacency matrix using fuzzy relation. Based on the centrality measurements, from Lasioglossum japonicum’s point of view, the keystone species for the each following years are Hedyotis lindleyana, Lysimachia japonica, Agrimonia pilosa and Ranunculus japonicus. While from the Lasioglossum ohei’s point of view, the keystone species for each following years are Circaea mollis, Lysimachia japonica, Impatiens textori and Lysimachia clethroides.